Confocal Laser Scanning Microscopy Analysis of 10 Cases of Craniofacial Fibrous Dysplasia. (August 2015) - Laino, Luigi; Favia, Gianfranco; Menditti, Dardo; De Francesco, Francesco; Salerno, Carmen; Scivetti, Michele; Serpico, Rosario; Lucchese, Alberta
Abstract Fibro-osseous lesions (FOL) represent a heterogeneous group of lesions that exhibit a variety of clinic-pathological features. Recently, based on the new World Health Organization classification system, these lesions were reclassified as follows: (1) fibrous dysplasia (FD), (2) osseous dysplasia, and (3) ossifying fibroma. Nevertheless, the nosologic placement of FOL may be problematic because of substantial overlap in the histopathological findings. In this study, we analyzed 10 cases of FD by both optical and confocal laser scanning microscopy, a research technique based on the laser light microscopic analysis of stained biological samples that allows improved tissue imaging and bidimensional pictures with high resolution at the cellular level to provide a better understanding of the diagnosis of this disease.